Performance Analysis of Finite-Time Generalized Proportional Integral Observer for Uncertain Brunovsky Systems - Rsetam, Kamal; Afsar, Raja Fawad; Cao, Zhenwei; Man, Zhihong (International Conference on Advanced Mechatronic Systems, 2023)
This paper proposes a novel finite-time generalized proportional integral observer (FTGPIO) based a sliding mode control (SMC) scheme for the tracking control problem of high order uncertain systems subject to fast time-varying disturbances. For this purpose, the construction of the controller consists of two consecutive steps. First, the novel FTGPIO is designed to observe unmeasurable plant dynamics states and disturbance with its higher time derivatives in finite time rather than infinite time as in the standard GPIO. In the FTGPO estimator, the finite time convergence rate of estimations is well achieved, whereas the convergence rate of estimations by classical GPIO is asymptotic and slow. Secondly, on the basis of the finite and fast estimations, the SMC scheme is constructed in order to compensate estimation errors in both states and disturbance. Finally, the tracking efficiency is verified by carrying out many simulations on the application example of flexible joint robot (FJR). Besides, comparing the proposed method with the standard GPIO based SMC method is performed.